FAKTOR YANG MEMPENGARUHI PEMBENTUKAN UNDANG-UNDANG - Kuswan Hadji; Fulvian Dzaki Zada; Salsabila Nurvan Aayusha; Achmad Rizky Airlangga; Nadia Manihuruk (Cahaya Ilmu Bangsa, 2024)
Regulations are provisions that bind members of society and are used as a guide, order and control of behavior. Regulations are made to regulate everything so that human life becomes orderly and as desired. Regulations have a general, abstract and continuous nature, this means that a regulation is expected to be realized with a high level of relevance to guarantee control of behavior and limit the authority of government organs so that there is no arbitrariness in running a state government, needs Regulations by society are influenced by various factors, including the need for regulations and protection in carrying out state life. This must be the main achievement in implementing regulations, which must pay attention to the sociological and ontological aspects of society/government organs as the subject of regulations (subject of law). Good regulations are regulations that can maximize aspects of national and state life by prioritizing Pancasilaism and the noble ideology of the Indonesian nation